2022
DOI: 10.3390/pr10010104
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Surface Modification of Epoxy Polymer in Air DBD and Gliding Arc

Abstract: We studied the epoxy polymer surface modification using air plasma treatment in a Gliding Arc (GA) plasma reactor and a pulsed Dielectric Barrier Discharge (DBD). We employed optical emission spectroscopy (OES) measurements to approximate the vibrational and rotational temperatures for both plasma sources, as well as surface temperature measurements with fiber optics and IR thermography to corelate with the corresponding hydrophilization of the epoxy material. Water contact angle measurements revealed a rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The efficiency of plasma treatment on different materials has been assessed in various studies, such as in [ 33 ] treating poly(lactide) (PLA) films by diffuse coplanar surface barrier discharge plasma, in [ 34 ] it was treated by oxygen plasma the silicon, silicon dioxide and glass, in [ 35 ] it was treated biaxially oriented polypropylene (BOPP) film by corona discharge or [ 36 ] epoxy polymer in air DBD and gliding arc, the results showing significant effects of the plasma treatment on polymeric surfaces. The most common surface modifications reported refer to wettability increasing of treated surfaces, surface oxidation, increase of adhesion forces and morphological changes,…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of plasma treatment on different materials has been assessed in various studies, such as in [ 33 ] treating poly(lactide) (PLA) films by diffuse coplanar surface barrier discharge plasma, in [ 34 ] it was treated by oxygen plasma the silicon, silicon dioxide and glass, in [ 35 ] it was treated biaxially oriented polypropylene (BOPP) film by corona discharge or [ 36 ] epoxy polymer in air DBD and gliding arc, the results showing significant effects of the plasma treatment on polymeric surfaces. The most common surface modifications reported refer to wettability increasing of treated surfaces, surface oxidation, increase of adhesion forces and morphological changes,…”
Section: Discussionmentioning
confidence: 99%
“…Especially with the blessing of nanosecond pulse power supply, brilliant nanosecond plasma discharges with high energy efficiency, intense reactivity, and low temperature have shown extraordinary potential in green, sustainable and low-carbon-emission material surface processing. However, with the deepening of the atmospheric pressure DBD application field, especially in the surface modification of large-scale insulation materials [9,10], the size and structure of typical DBD reactors (∼cm) are far from reaching the industrial demand (∼m). Hence, improving the scale of nanosecond-pulse DBD plasma for higher treatment efficiency with low power consumption conditions is of great significance, which is the key to further industrializing DBD in various fields.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of GAD plasma compared to other non-thermal plasmas are its high processing efficiency, high electron temperature and density, simple configuration, and the easy control of its process parameters [8][9][10][11][12][13][14][15][16][17][18][19][20]. It has been observed that GAD plasma is very widely used for plasma reforming and fuel and waste treatment [12][13][14][15][16], and it could be also used for bacterial inactivation and food decontamination [10,[17][18][19][20], the creation of plasma-activated water [5,8,21], and surface treatments and modifications [22][23][24][25][26]. Gliding arc discharge characteristics such as current and voltage values, the arc column length, discharge duration, density, and type of species produced in the plasma are strongly affected by the geometry and configuration of the electrodes, the experimental parameters, and the type of gas used for the plasma's generation [13,16,18,20].…”
Section: Introductionmentioning
confidence: 99%